Estado de exceção e estado democrático de direito: violência e poder no pensamento de Walter Benjamin - Santos, André Ricardo Dias (2019)
Our thesis work is situated in the criticism of the modern state, especially in the form that this assumes in the historical context of the first half of the twentieth century. Here, the state starts to act from the rule of exception, which means to say that it acts on a contradiction guided by the binomial inclusion-exclusion of individuals through the Law. We start from this debate found in Walter Benjamin's work to investigate the conditions of democracy and sovereignty today. To this end, we investigate the problem in the work of the German philosopher through his philosophy of history, which functions as the method for ascertaining the historical conditions of class struggle and for proposing a new historical paradigm found in understanding the tradition of the vanquished. From then on, we look at the concept of state of exception, in search of its forms, namely, the state of permanent exception and the “true” state of exception. In this journey, we seek to understand the concept of sovereign power by the articulation between two forms, the constituent power and the constituted power to then think the antithesis of the destituent power, a concept which conforms to the introduction of the emergence of the true exception. These questions are guided by the idea of criticism of violence, a concept present in Benjamin’s thought in two moments: as violence that founds the exception and as another type of violence, that disrupts its mythical circuit in the form of law. We are going to investigate the philosophical question of the state of exception to point out in the work of the German philosopher the understanding that sovereign power and its representational mechanism form a type of violence from its origin, substantiated by the paradigm of sovereignty. This criticism of representation supports the problem of democratic achievement, which is expressed in the hypothesis that the rule of law includes the state of exception as a necessity of its operation, which enables us to defend revolutionary violence, here, in the way Benjamin defines it, as pure violence.